The Influence of Zakat Local Regulation Practice No. 6 of 2013 Towards the Distribution of Zakat in Siak Regency (Case Study of BAZNAS in Siak Regency) - Candri, Kiki; Kirmizi, Kirmizi; Rasuli, Rasuli (International Journal of Economic, Business & Applications, 2019)
This study aims to determine the development of zakat in Siak Regency, to find out the influence of Zakat Local Regulation No. 6 of 2013on the distribution of zakat in Siak Regency. The research methodology of the data in this study was by collecting primary data directly from original sources such as agencies and companies that became research subjects, and conducted interviews with respondents. The sampling technique in this study uses a non-probability technique that is saturated sample or total sampling which is census, the object used is the administrator of BAZNAS and UPZ in Siak Regency, amounting to 75 people. In the analysis phase, data quality test, validity test, reliability test, classic assumption test, data normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, and Hypothesis test (T test and F test). The results showed that the Zakat Local Regulation had a significant effect on the distribution of zakat in Siak Regency which was in accordance with the basic principles of the Zakat Local regulation No, 6 of 2013, namely Islamic Sharia, trustworthiness, expediency, justice, legal certainty, accountability.